Evaluasi Sistem Drainase terhadap Genangan Air pada Ruas Jalan Malangbong-Wado di Kabupaten Garut - Fitriyadi, Adi; Permana, Sulwan (Jurnal Teknik Sipil, 2024)
Heavy rainfall causes drainage channels to handle excess water. Puddles and flooding often occur on the 50-meter section of Malangbong-Wado Road, necessitating an evaluation to ensure the drainage system is functioning properly. This research employs a quantitative approach, processing rainfall through a frequency distribution and testing it using the Chi-Quadrat and Smirnov-Kolmogorov methods. The rational method calculated the rainfall intensity and determined the five-year return period for flood discharge. The analysis results indicate that the drainage channel is unable to accommodate the planned discharge, necessitating an evaluation to ensure that the channel Q (Qs) exceeds the planned Q (Qr) or Qs >Qr. The average channel Q value was 2.51 m3/second, and the plan Q was 1.50 m3/second, according to the results. Thus, the channel, with dimensions of 0.8 meters wide and 1.00 meters high, can accommodate the discharge plan. Simulation results using SWMM V5.1 software demonstrate that channels with these dimensions can accommodate discharge plans.